A pilot study with 3D T1ρ-mapping for quantitative evaluation of cartilage after open-wedge high tibial osteotomy. Issue 151 (June 2022) - Yamasaki, Tsuyoshi; Ogawa, Munehiro; Okamura, Kensuke; Inagaki, Yusuke; Tanaka, Yasuhito
Graphical abstract: Highlights: 3D T1p-mapping was developed to evaluate cartilage changes after open-wedge HTO. Eleven patients with medial knee osteoarthritis were evaluated with 3D T1p-mapping. 3D T1ρ-mapping detected changes in knee joint cartilage quality after OWHTO. 3D T1ρ-mapping is effective in detecting changes in cartilage quality after OWHTO. Abstract: Purpose: To evaluate the recently developed three-dimensional (3D) T1ρ-mapping technique for the quantitative evaluation of cartilage changes after open-wedge high tibial osteotomy (OWHTO). Method: Eleven patients with medial knee osteoarthritis and spontaneous osteonecrosis of the medial femoral condyle underwent T1ρ magnetic resonance imaging. The full-thickness cartilage of the medial femoral condyle (MFC), lateral femoral condyle, medial tibial condyle, and lateral tibial condyle, and the trochlea and patella were set as regions of interest; mean T1ρ values were calculated using two-dimensional (2D) and 3D analyses. The state of cartilage injury was evaluated using the International Cartilage Repair Society grading system (ICRS grade). T1ρ values before OWHTO and after hardware removal were compared using the Wilcoxon signed-rank test. The correlation between T1ρ values and the ICRS grade was explored using the Spearman rank correlation coefficient. Results: Cartilage repair at the MFC was observed in a high proportion of patients (82%), but 2D analysis did not reveal a significant difference after surgery at any site. In contrast, 3D analysis revealed a significant decrease in T1ρ values after surgery at the MFC (before surgery: 44.1 ms; after surgery: 38.9 ms; p  = 0.016), but no significant difference at any other site. In the MFC, there was a positive correlation between 3D T1ρ values and arthroscopic findings before and after surgery (rs = 0.62, p  < 0.01), which was absent from the 2D T1ρ values. Conclusions: 3D T1ρ-mapping may be an effective tool for detecting changes in cartilage quality after OWHTO.